Pengaruh Job Insecurity, Emotional Exhaustion dan Self Efficacy terhadap Kinerja Karyawan Kontrak di Bandar Lampung - Nurul Atika Rohmah; Nira Dian Kinanti; Rio Riandi; Vicky F Sanjaya (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2020)
This study aims to examine job insecurity, self-efficacy and emotional exhaustion on the performance of contract employees in Bandar Lampung. The method used is using a questionnaire. The sample is 50 respondents. The statistical test was carried out using Statistic Structural Equation Modeling (SEM) based on Partial Least Square (PLS) version 3. The validity test used the loading factor value, while the reliability test used the cronbach'c alpha value, composite reliability and Average Variance Extracted (AVE) produced indicators. valid and reliable. Hypothesis testing produces job insecurity and emotional exhaustion which has a positive and insignificant effect, while self-efficacy has a positive and significant effect in improving the performance of contract employees in Bandar Lampung.